DOES THE RISE OF ISLAMIC CONSERVATISM THREATEN INDONESIAN DEMOCRACY? - Tanashur, Panji (UIN Mataram, 2021)
the rise of Islamist narrative and agenda is found in the political parties categorized as Indonesian secular parties. None of them is an Islamist party, but the Islamist narratives seem prevalent. The role of ormass in vernacularizing seems significant since the Islamist interest was discovered as the policy product and a trend in Indonesian Muslims, especially the millennials. Seeing the proliferation, the political party might compromise with the broader market of the constituency. Meanwhile, the assumption that NU and Muhammadiyah as the antidotes of Islamic radicalism might not a hundred percent correct since they show a weakening of their influence within their members. It can be seen from the neglect of the fatwas issued, advice, and their prohibitions by both NU and Muhammadiyah member. Besides, the presence of the MUI, which is fully supported by the government in issuing fatwas, has actually created controversy because the fatwa issued was mostly accommodated by the Islamist Agenda. This condition is reinforced by the membership recruitment system as well as applying the equal quota system even some of them are from NU and Muhammadiyah that possess the most significant mass base. The recruitment system certainly makes it easier for extremists to control and dominate the membership of MUI. Some moderate Islamic scholars who criticized the action of defending Islam reaped ridicule and bullies from the demonstrators. On the other hand, they continue to appraise Rizieq Syihab as a central figure in the Islamic defense action. The descriptions above illustrate that the dominance of Islamic radicalism in Indonesia, which I consider a threat to the progress of Indonesian Democracy. The above claims were revealed after some comprehensive research through the data that were collected from some related literature, magazines, jounals, and other sources. The data is analysed from the phenomenon happened which were compared to the current reality in some places which can be confirm through the electronic or non-electronic media. These are the claims from the writers which need further analysis.